Evaluation of Feed Strategies and Changes of Stocking Rate to Decrease the Carbon Footprint in a Traditional Cow-Calf System: A Simulation Model - Toro-Mujica, Paula (Frontiers in Veterinary Science, 2021)
One of the main production challenges associated with climate change is the reduction of carbon emissions. Increasing the efficiency of resource utilization is one way to achieve this purpose. The modification of production systems through reproductive, genetic, feed, and pastoral management practices have been proposed as alternatives to increasing technical-economic efficiency, even though the "environmental viability" of these modifications has not always been evaluated. With the aim of simulating production performance and estimating the carbon footprint (CF) of modifications to the traditional cow-calf system, a simulation model was developed by adaptation of a previous model. Adaptations of the model included the quantification of emissions and the possibility of adding carbon sequestration in pasture and soil. The modifications evaluated corresponded to combinations of stocking rate, use of creep feeding practices with different supplementation levels, and the incorporation of feed additives in the supplement, using factorial experiments. Additionally, the scenarios were evaluated with and without carbon sequestration. The carbon footprint for the base scenarios was 12.5±0.3 kg of CO2-eq/kg of live weight (LW) when carbon sequestration was considered, and 13.0±0.4 kg of CO2-eq/kg of LW, in the opposite case. Changes in stocking rate, supplementation level, and consideration of carbon sequestration in pasture and soil had a significant effect on the carbon footprint in all simulated scenarios. The inclusion of additives in the supplement did not have a significant effect on production costs. The developed model makes possible the selection of feed strategies or management adaptations environmentally viable.